Effect of CaCl2 Crosslinker Concentration On The Characteristics, Release and Stability of Ciprofloxacin HCl-Alginate-Carrageenan Microspheres - Amiruddin; Muh. Agus Syamsur Rijal; Dewi Melani Hariyadi (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2023)
Background: Ciprofloxacin HCl is a broad-spectrum fluoroquinolone antibiotic that has the lowest MIC against Mycobacterium tuberculosis but has limitations in oral use, so inhalation microspheres are made. Objective: This study aimed to investigate the effect of CaCl2 crosslinker concentration on the characteristics, release and stability of ciprofloxacin-alginate-carrageenan microspheres. Methods: Microspheres were prepared by ionotropic gelation using aerosolization with calcium chloride 0.5M (F1), 1.0M (F2), 1.5M (F3), 2.0M (F4) as crosslinker and then dried using freeze dryer. Results: Ciprofloxacin-alginate-carrageenan microspheres formed of yellowish-white powder, smooth morphology and excellent flow properties with the particle size of less than 5µm, drug loading and entrapment efficiency were between    2.05% - 2.42% and 75.34% - 98.09%, yield was between 84.69% - 97.57%, moisture content of less than 10%. Ciprofloxacin-alginate-carrageenan microspheres with 1.5M crosslinker (F3) was the optimal formula. For 12 hours, ciprofloxacin released was 49.89% - 63.78% at pH 7.4, and the kinetics of drug release showed that of Korsmeyer-peppas with a mechanism based on fickian diffusion. The microspheres were discovered to be stable for up to 28 days of storage. Conclusion: The increased concentration of the CaCl2 crosslinker from 0.5M to 2.0M decreased the particle size and drug release but increased the yield, drug loading and entrapment efficiency.